Estudo do sistema proteolítico de Callosobruchus maculatus (gorgulho do feijão) durante seu desenvolvimento - Lopes, Ana Lúcia Serra (1985)
During the development of the beetle Callosobruchus maculatus, an alkaline and an acid proteolytic activities, as well as an acid prosphatasic an alfa-amylasic and an anti-chymotriptic activities were detected. [...]